Characteristics of eye-related emergency visits and triage differences by nurses and ophthalmologists: Perspective from a single eye center in southern China - Chen, Juan; Chen, Chen-Mei; Zheng, Yongxin; Zhong, Liuxueying (Frontiers in Medicine, 2023)
Purpose To describe characteristics of eye-related emergency department (ED) visits and investigate differences in priorities assigned to patients by triage nurses and ophthalmologists. Methods A prospective survey was conducted at the ED of Zhongshan Ophthalmic Center from January 1, 2021, to May 31, 2021. Clinical data from patients with acute ophthalmic conditions lasting less than 7 days were collected via a standard questionnaire and the urgency levels assigned by nurses and physicians were also recorded. Binary logistic regression was performed to identify characteristics associated with truly emergency conditions and up- or down-triage. Results A total of 1907 patients were enrolled, with 582 (30.5%) classified as “non-emergency.” Red eye (69.7%), eye pain (53.0%), ocular trauma (44.1%), tearing (43.6%), and blurred vision (43.1%) were the most common complaints. Truly emergency tended to be male (OR 2.019, p < 0.001) and with unilateral eye involvement (OR 2.992, p < 0.001). Nurses prioritized conjunctival, scleral, closed ocular trauma and eyelid diseases over doctors while giving less priority to open ocular trauma, cornea, uveitis, and vitreoretinal diseases (p < 0.05). Overemphasis on mild blurred vision (OR 3.718, p = 0.001) and insufficient understanding of conjunctival diseases without red eye (OR 0.254, p = 0.001) were associated with conjunctival disease “up-triage.” Insufficient awareness of moderate and severe blurred vision was associated with “down-triage” for ocular trauma (OR 3.475, p = 0.001 and OR 2.422, p = 0.020, respectively). Conclusion Ophthalmic EDs are typically flooded with patients suffering from acute ocular problems, with a considerable portion for non-emergency conditions. The identification of characteristics associated with truly emergency cases and nurses’ triage preferences is valuable in providing target guidance for future ED practice and facilitating the proper allocation of emergency resources.